Multiplayer online game for distance learning for Integrated Islamic Kindergarten students of Khairunnisa - Susi Nurindahsari; Nurul Arifiah Gunarsih; Muhamad Zaim Zamzami; Syahrul Adi Mustofa; Irfan Triadi Saputra; Dwi Intan Af’idah (Universitas Muhammadiyah Magelang, 2022)
During the Covid-19 pandemic, education in Indonesia was delivered via distance learning (PJJ). Of course, this learning is fraught with difficulties, particularly for kindergarten students who require direct teacher guidance. The IT Khairunnisa Kindergarten, which is located in Grinting Village, Bulakamba District, Brebes Regency, is no exception. As a result, innovative solutions are required to ensure that learning can take place more effectively even when it is done remotely. The innovative solution is a multiplayer online game that includes learning elements such as counting, matching, and others as a learning medium for students and teachers. This community service is carried out by socializing and assisting teachers and students in the use of learning game apps. When the socialization took place, participants were very enthusiastic about learning this application, particularly students, who carefully observed how the game was used and the features in it. The interview results revealed that the participants were interested in using the game as a medium for PJJ, and the students were interested in this game as well, because learning was like playing. This application is simple to use and interactive, making it possible to perform online KBM that feels like offline KBM.